Salmonella Prophages, Their Propagation, Host Specificity and Antimicrobial Resistance Gene Transduction - Lisa Trofeit; Elisabeth Sattler; Johannes Künz; Friederike Hilbert (Antibiotics, 2023)
Salmonella enterica subsp. enterica is a zoonotic bacterial pathogen that causes foodborne outbreaks in humans. Lytic bacteriophages to control Salmonella in food production are already being used in scientific studies and some are commercially available. However, phage application is still controversial. In addition to virulent phages, which are used in phage therapy and lyse the bacterial host, lysogenic phages coexist in the environment and can reside as prophages in the bacterial host. Therefore, information about Salmonella prophages is essential to understand successful phage therapy. In 100 Salmonella food isolates of the serovars Enteritidis and Typhimurium, we propagated prophages by oxidative stress. In isolates of the serovars Typhimurium and Enteritidis, 80% and 8% prophages could be activated, respectively. In the phage lysates from the serovar Typhimurium, the following antibiotic resistance genes or gene fragments were detected by PCR: sul1, sul2, blaTEM, strA and cmlA; however, no tetA,B,C, blaOXA, blaCMY, aadA1, dfr1,2 or cat were detected. In contrast, no resistance genes were amplified in the phage lysates of the serovar Enteritidis. None of the phage lysates was able to transduce phenotypic resistance to WT 14028s. Most of the prophage lysates isolated were able to infect the various Salmonella serovars tested. The high abundance of prophages in the genome of the serovar Typhimurium may counteract phage therapy through phage resistance and the development of hybrid phages.